Tradução comentada do texto Análisis ideológica de los tiempos de la conjugación castellana: indicativo, de Andrés Bello, para estudantes brasileiros de espanhol - Lima, Ana Kelly de Souza (2023)
Análisis ideológica de los tiempos de la conjugación castellana is a very relevant work for the constitution of Spanish grammar, bringing numerous philosophical and linguistic contributions on this theme. Its author, Andrés Bello (1781-1865), is considered the most important intellectual figure in the context of 19th century Hispano-American culture, and his political and literary works are an important part of this culture. Humanist, diplomat, poet, legislator, philosopher, educator, and Venezuelan philologist, these are some of the names attributed to Bello. This research is justified both by socio-historical and cultural issues concerning the figure of the author under study with his contributions in various areas of knowledge, and by the relevance of the translated text, which presents a rupture with the Latin model of verb conjugations, bringing innovative aspects regarding the use of verb tenses, which will help in the constitution of a model of nomenclature and conjugation within Spanish grammar, later recognized by the Royal Spanish Academy. The objective of this work consists in the elaboration of an annotated and commented translation through an approach with didactic purposes, and we hope that the divulgation of this study may contribute to the process of language teaching and learning, whether it is a mother tongue or a foreign language. As methodology of this work, we opted for qualitative research, which comprises a bibliographical research with presentation of the writer’s life and work, in order to better understand Bello’s writings, and the production of the annotated translation, followed by theoretical discussions based on Translation Studies focused on equivalence issues involving the difficulties and problems of translation (NORD, 2009). Among the theoretical references used are Hurtado Albir (2001), Pym (2016), Catford (1980), Jakobson (1989), Vinay and Dalbernet (1958), Berman (1986, 1989, 2007), Williams and Chesterman (2002) and Nord (2009), based on which a brief overview of Translation Studies as an autonomous discipline was made, independent from Linguistics. We also discuss the definition of translation of specialized texts and of commented translation and its structures (TORRES, 2017; FREITAS, 2016), and the concept of equivalence (COSTA, 1992).